RNA-based Vaccines against SARS-CoV-2: A Word of Caution and an Analysis of Potential Long-term Adverse Events - Gambacorti-Passerini, Carlo; Aroldi, Andrea (Organisms. Journal of Biological Sciences, 2022)
This paper briefly discusses the mechanism and potential of still unknown side-effects of RNA-based vaccines against SARS-CoV-2.